Comparison of estimation methods for the density of autoregressive parameter in aggregated AR(1) processes - Celov , Dmitrij; Leipus, Remigijus; Kvedaras, Virmantas (Lietuvos matematikos rinkinys, 2021)
The article investigates the properties of two alternative disaggregation methods. First one, proposed in Chong (2006), is based on the assumption of polynomial autoregressive parameter density. Second one, proposed in Leipus et al. (2006), uses the approximation of the density by the means of Gegenbauer polynomials. Examining results of Monte-Carlo simulations it is shown that none of the methods was found to outperform another. Chong’s method is narrowed by the class of polynomial densities, and the secondmethod is not effective in the presence of common innovations.Bothmethodswork correctly under assumptions proposed in the corresponding articles.
Keywords: random coefficientAR(1); aggregation; disaggregation; long memory; mixture density